2021
DOI: 10.1111/ciso.12402
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Urban Precarity

Abstract: Cities have long been associated with precarity. This link seems to have intensified under contemporary global regimes of capitalism, with both popular and academic discourses noting the risks that come with building and inhabiting urban environments. The introduction to this special issue reflects on the various ways in which anthropology has engaged with the relationship between “urbanity” and “precarity.” It argues that current work on precarity either favors the experiences of the Global North or sidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Despite being messy and unstable, the everyday reality at the shopping center is treated by many with acceptance and compromise (Archambault, 2021;Campbell and Laheij, 2021). Difference was normalized in comments such as, "it is what it is," "people need to be somewhere anyway," or "let all flowers blossom.…”
Section: S Tab Ilit Y Amid Ins Tab Ilit Ymentioning
confidence: 99%
See 4 more Smart Citations
“…Despite being messy and unstable, the everyday reality at the shopping center is treated by many with acceptance and compromise (Archambault, 2021;Campbell and Laheij, 2021). Difference was normalized in comments such as, "it is what it is," "people need to be somewhere anyway," or "let all flowers blossom.…”
Section: S Tab Ilit Y Amid Ins Tab Ilit Ymentioning
confidence: 99%
“…While such work highlights the agency of individuals to manage their own lives, resolving instabilities with temporary solutions might only steer the person from one form of precarity to another, and expose them to other risks (Campbell and Laheij, 2021;Muñoz, 2018a). So far, the vignettes have suggested that coping with precarity requires informal acts of labor, another key aspect of precarity that emerges on the street.…”
Section: Tac Ti C S On the S Tree Tmentioning
confidence: 99%
See 3 more Smart Citations